Metabolic glycan labeling-assisted discovery of cell-surface markers for primary neural stem and progenitor cells. Issue 43 (14th May 2018) - Bai, Qing-Ran; Dong, Lu; Hao, Yi; Chen, Xing; Shen, Qin
Abstract : Metabolic labeling with azidosugars in a neural stem cell (NSC)-enriched endothelial coculture followed by mass-spectrometry profiling identifies sialoglycoproteins on NSCs. Abstract : A chemical approach was developed for identifying cell-surface markers for primary neural stem cells (NSCs). Using an in vitro coculture system of primary NSCs combined with metabolic labeling of sialoglycans with bioorthogonal functional groups, we selectively enriched and identified a list of cell-surface sialoglycoproteins that were more abundantly expressed in neural stem and progenitor cells.